Hypertrophic obstructive cardiomyopathy: review of surgical treatment. (November 2017) - Price, Jonathan; Clarke, Nicholas; Turer, Aslan; Quintana, Eduard; Mestres, Carlos; Huffman, Lynn; Peltz, Matthias; Wait, Michael; Ring, W Steves; Jessen, Michael; Bajona, Pietro
Hypertrophic cardiomyopathy ranks among the most common congenital cardiac diseases, affecting up to 1 in 200 of the general population. When it causes left ventricular outflow tract obstruction, treatment is guided to reduce symptoms and the risk of sudden cardiac death. Pharmacologic therapy is the first-line treatment, but when it fails, surgical myectomy or percutaneous ablation of the hypertrophic myocardium are the standard therapies to eliminate subaortic obstruction. Both surgical myectomy and percutaneous ablation are proven safe and effective treatments; however, myectomy is the gold standard with a significantly lower complication rate and more complete and lasting reduction of left ventricular outflow tract obstruction.